Strategi Pelaksanaan Pengarusutamaan Gender (PUG) dalam Pendidikan - Hermina, Dina (IAIN Antasari Banjarmasin, 2014)
Some studies on the implementation of gender mainstreaming program in Indonesia, especially in the field of education, indicates the failure of Indonesian government. An obscurity of concept of structured gender role in Indonesia is associated with the term of âpengarusutamaan genderâ which is adapted from English languageâgender mainstreaming. In the reality, there is a misconception and conflict in elaborating the case of gender bias and stereotypical gender role. Gender inequality and traditional roles of each gender has rooted in the idea of Indonesian society, culture and religion; and it has accumulated become a major obstacle.